Medicinal Plants in Poultry During Post‐Antibiotic Era in One‐Health Approach: An Extensive Review - Alireza Talebi; Arman Savari (Veterinary Medicine and Science, 2026)
ABSTRACT Background Increasing drug resistance, together with possible transmission of these phenomena to other pathogenic agents, as well as the dissemination of resistant microbes and drug residues to the environment, poses existing challenges for human health. The journey in history of medicine indicates that the post‐antibiotic era has been initiated and the application of medicinal plants is a promising alternative to antibiotics. Objectives The aim of this review was to have a glance at available medicinal plant products in modern poultry production in the post‐antibiotic era. However, the globalization of one‐health needs efforts from both scientists and policy makers to work firmly in a harmonized mission continuously, and all nations must be simultaneously involved in this process to fulfil their obligation properly. Methods This review is focused on the role of the well‐known medicinal plants in poultry and method of reviewing includes a brief introduction, history, the present status and prospective future by critical reviewing the published literatures. Results An extensive application of natural medicine in poultry during the post‐antibiotic era in a comprehensive holistic one‐health was reviewed, and some of the most relevant commercially available products were also mentioned as a footprint to encourage the researchers to include all the necessary parameters for practical application of the medicinal plant products during their study in details. Some recommendations/future directions on achieving the goals and completing the mission were also proposed. Conclusion Application of the medicinal plants in intensive poultry industry is the best solution for production of antibiotic‐free foods during the post‐antibiotic era.